[PP.05.14] PREVALENCE OF HYPERKALEMIA IN MATCHED DIABETIC AND NON-DIABETIC PATIENTS WITH CHRONIC KIDNEY DISEASE: A NESTED CASE-CONTROL STUDY. (September 2016) - Loutradis, C.; Tolika, P.; Skodra, A.; Avdelidou, A.; Sarafidis, P.
Abstract : Objective: Hyperkalemia is a frequent and potentially life-threatening electrolyte disorder, usually complicating chronic kidney disease (CKD). Factors superimposed to reduced renal function, are further elevating the risk for hyperkalemia development, but their contribution is not fully elucidated in relevant literature. This study aimed to compare the prevalence of hyperkalemia in matched diabetic and non-diabetic patients with CKD and to evaluate factors associated with hyperkalemia occurrence. Design and method: This is a nested case-control study from a cohort of patients followed in a Nephrology outpatient clinic. A total of 180 type-2 diabetic and 180 non-diabetic patients with CKD matched for gender, age and eGFR, were included. Patients with type-1 diabetes or end-stage renal disease were excluded. Prevalence of hyperkalemia was defined as serum potassium > 5 mEq/L and/or use of sodium polystyrene sulfonate, and further by serum potassium levels >5 and greater or equal to 5.2 and 5.5 mEq/L. Prevalence was compared between the two study groups in total population and in CKD Stages separately. Univariate and multivariate logistic regression analysis were conducted to identify factors associated with hyperkalemia occurrence. Results: The prevalence of hyperkalemia was higher in diabetic CKD patients (27.2% vs 20%, p = 0.107) and remained around 30% higher with all secondary definitions used, but never reached statistical significance. In Stage 2 no difference was noted (8.7% vs 17.4%, p = 0.665), in Stage 3 prevalence was significantly higher in diabetics (28.6% vs 17.5%, p = 0.036) and in Stage 4 equally high in both groups (35.5% vs 32.3%, p = 0.788). In multivariate analysis, Stage 4 CKD (OR: 4.535, 95% CI: 1.561–13.173), use of angiotensine-converting enzyme inhibitors (OR: 2.228, 95%CI: 1.254–3.958), and smoking (OR: 2.254, 95%CI: 1.218–4.171) were independently associated with hyperkalemia. Conclusions: Diabetes mellitus is elevating the prevalence of hyperkalemia only in CKD Stage 3 patients (moderately impaired renal function) and this difference is attenuating in CKD Stage 4. Advanced CKD at Stage 4 and ACEIs are major determinants of hyperkalemia occurrence. As the vast majority of patients with CKD belong to Stage 3, the presence of diabetes must be appreciated regarding hyperkalemia risk and relevant therapeutic decisions.